Bleak - (:unkn) unknown (My University, 2023)
Το μουσικό έργο με τίτλο «Bleak» ολοκληρώθηκε στον Πειραιά, τον Ιανουάριο του έτους 2022, στα πλαίσια της διπλωματικής εργασίας της συνθέτριας Αλεξάνδρας Τσουκαλά, προπτυχιακής φοιτήτριας του Τμήματος Μουσικών Σπουδών του Ιονίου Πανεπιστημίου.

The musical project entitled "Bleak" was completed in Piraeus, in January of the year 2022, in within the framework of the diploma thesis of the composer Alexandra Tsoukala, an undergraduate student of the Department of Music Studies of the Ionian University.
Bleak
Keywords: Ορχηστρικό, Σύνθεση; Orchestra, Composition